Insulin–glucagon‐like peptide‐1 receptor agonist relay and glucagon‐like peptide‐1 receptor agonist first regimens in individuals with type 2 diabetes: A randomized, open‐label trial study. Issue 6 (8th February 2022) - Takeshita, Yumie; Kita, Yuki; Tanaka, Takeo; Goto, Hisanori; Nakano, Yujiro; Teramura, Chisato; Enyama, Yasufumi; Takamura, Toshinari; ,
Abstract: Aims/Introduction: Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA) might be less effective in patients with severe hyperglycemia, because hyperglycemia downregulated the GLP‐1 receptor in an animal study. To examine this hypothesis clinically, we compared the glucose‐lowering effects of GLP‐1 receptor agonist liraglutide with and without prior glycemic control. Materials and Methods: In an open‐label, parallel trial, participants with poorly controlled type 2 diabetes were recruited and randomized to receive once‐daily insulin therapy, degludec (Insulin–GLP‐1 RA relay group, mean 16.8 ± 11.4 IU/day), for 12 weeks and then liraglutide for 12 weeks or subcutaneous injections of GLP‐1 RA, liraglutide (GLP‐1 RA first group, 0.9 mg), for 24 weeks. The primary efficacy end‐points consisted of changes in the levels of fasting plasma glucose and glycated hemoglobin (HbA1c). Results: The median fasting plasma glucose and HbA1c before the study were 210.0 mg/dL and 9.8%, respectively. The levels of fasting plasma glucose and HbA1c significantly decreased in the Insulin–GLP‐1 RA relay group ( P  < 0.001) and GLP‐1 RA first group ( P  < 0.001) by week 24, although no intergroup differences were observed. The reduction of HbA1c in the Insulin–GLP‐1 RA relay group tended to be larger than that in the GLP‐1 RA first group in the lowest CPR (C‐peptide immunoreactivity) quartile ( P  = 0.072). The adverse events consisted of gastrointestinal problems, followed by hypoglycemia. Conclusions: The GLP‐1 receptor agonist is overall effective without prior glycemic control with insulin in participants with poorly controlled type 2 diabetes. However, in participants with insulinopenic type 2 diabetes, prior glycemic control with insulin might overcome glucose toxicity‐induced GLP‐1 resistance. Abstract : The glucagon‐like peptide‐1 receptor agonist is overall effective without prior glycemic control with insulin in participants with poorly controlled type 2 diabetes. However, in participants with insulinopenic type 2 diabetes, prior glycemic control with insulin might overcome glucose toxicity‐induced glucagon‐like peptide‐1 resistance.